Design of Chebychevâs Low Pass Filters Using Nonuniform Transmission Lines - Said Attamimi; Mudrik Alaydrus (Journal of ICT Research and Applications, 2015)
Transmission lines are utilized in many applications to convey energy as well as information. Nonuniform transmission lines (NTLs) are obtained through variation of the characteristic quantities along the axial direction. Such NTLs can be used to design network elements, like matching circuits, delay equalizers, filters, VLSI interconnections, etc. In this work, NTLs were analyzed with a numerical method based on the implementation of method of moment. In order to approximate the voltage and current distribution along the transmission line, a sum of basis functions with unknown amplitudes was introduced. As basis function, a constant function was used. In this work, we observed several cases such as lossless and lossy uniform transmission lines with matching and arbitrary load. These cases verified the algorithm developed in this work. The second example consists of nonuniform transmission lines in the form of abruptly changing transmission lines. This structure was used to design a Chebychevâs low pass filter. The calculated reflection and transmission factors of the filters showed some coincidences with the measurements.